Investigating air entrapment in biocemented composites for geotechnical ground improvement - Gomez, Michael G.; Martinez, Erick M.; Ribeiro, Bruna G. O.; Tai, Chung-En (Frontiers in Built Environment, 2025)
Biocementation is a biomediated ground improvement method that can improve the engineering behavior of granular soils through the precipitation of calcium carbonate minerals. Although cemented bonds and particle coatings generated from biocementation can enable large increases in soil initial shear stiffness, peak shear strength, and liquefaction resistance; emerging strategies such as soil desaturation have shown the ability of alternative mechanisms to enable large improvements in liquefaction behaviors. This article highlights outcomes from recent experiments which have investigated the potential of novel treatment processes to enable the generation and entrapment of gases within biocementation. We hypothesize that these entrapped gases may provide a secondary mechanism to improve soil undrained shearing behaviors by enabling the release of gases following cemented bond deterioration and related increases in pore fluid compressibility. Our study employs a series of batch experiments to identify new methods to both generate and entrap gasses within an organic polymer layer applied intermittently between biocementation treatments. Biocemented composites resulting from this work may enable large improvements in the environmental and financial efficacy of biocementation and the resilience of treated soils to extreme loading events.